2012
DOI: 10.1016/j.jfma.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis virus infection in men who have sex with men aged 18–40 years in Taiwan

Abstract: HIV-positive MSM have a higher seroprevalence rate of HBV and HCV infection than HIV-negative MSM in Taiwan. Vaccination and safe-sex counseling should be provided to prevent the transmission of hepatitis viruses among MSM who may be engaged in high-risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 43 publications
4
25
1
Order By: Relevance
“…Infections in HIV-infected individuals were predominately due to genotype 1a viruses and found only in males possibly reflecting un-reported sex between men. In addition to drug use, the observation of transmission in known HIV positives is not surprising with recent studies from high income countries have demonstrated a high incidence of recent HCV infections in HIV-infected MSMs [8,18,23,[25][26][27][29][30][31][33][34][35][36]. Recent PHE data demonstrated a 21% increase in new HIV infections amongst MSMs in London since 2011 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Infections in HIV-infected individuals were predominately due to genotype 1a viruses and found only in males possibly reflecting un-reported sex between men. In addition to drug use, the observation of transmission in known HIV positives is not surprising with recent studies from high income countries have demonstrated a high incidence of recent HCV infections in HIV-infected MSMs [8,18,23,[25][26][27][29][30][31][33][34][35][36]. Recent PHE data demonstrated a 21% increase in new HIV infections amongst MSMs in London since 2011 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies reported the prevalence of HCV infection in high-risk populations: ten were from China [17][18][19][20][21][22][23][24][25][26], two from Japan [27,28], two from Korea [29,30] and five from Taiwan [12,[31][32][33][34]. Among high-risk populations, the prevalence of HCV infection was higher among IDUs (48-95 % in China, Table 4).…”
Section: Prevalence Of Hcv Infection In High-risk Populationsmentioning
confidence: 99%
“…4 Non-IDU HCV acquisition is rarely identified among HIV-negative MSM in Australia and overseas, [98][99][100] with an HCV prevalence of under 1% among HIV-negative non-IDU MSM overseas, arguing against routine HCV testing among HIV-negative MSM. [101][102][103][104] Recently, the US Multicenter AIDS Cohort Study reported an association of incident HCV with higher numbers of receptive unprotected anal intercourse partners, as well as IDU and HIV-positive status. Nonetheless, HCV incidence was only 0.5 per 1000 PY in HIV-negative MSM compared with 4.2 per 1000 PY in HIV-positive MSM.…”
Section: Hepatitis C Virusmentioning
confidence: 99%